African dynamics in a multipolar world - Engel, U.; Ramos, M. J. (2013)
Fifty years after the foundation of the OAU and the consolidation of most African states and institutions, the international panorama and Africa’s position in it have changed considerably. The world's geopolitical and economic configuration has evolved, with new actors appearing in a new period of globalization. In tone with ECAS 2013, this volume proposes that the experiences appearing in Africa question dominant paradigms in terms of political practice and academic reflection and thus offer a clear challenge to the academic community. The volume offers clues to answer questions such as: What is the impact of the current processes of globalization for African countries and African citizens? How should African Studies be engaged to gauge African dynamics, both at a local and global level? What interdisciplinary means and tools should be brought in to produce an epistemologically relevant view (or narrative) of the issues under analysis?